Analysis of the paraglacial landscape in the Ny-Ålesund area and Blomstrandøya (Kongsfjorden, Svalbard, Norway). Issue 2 (9th December 2020) - Berthling, Ivar; Berti, Claudio; Mancinelli, Vania; Stendardi, Laura; Piacentini, Tommaso; Miccadei, Enrico
ABSTRACT: Ice cover changes have affected the Svalbard Islands during the Quaternary and conditioned a complex paraglacial landscape. In these remote and poorly vegetated arctic areas, the integration of field investigations and analysis of aerial images and DTMs or terrestrial laser scanning, is effective in the understanding landscape features and changes. In this work, we present the results of a geomorphological investigation and mapping in two sites along the Kongsfjorden in NW Svalbard (Ny-Ålesund and Blomstrandøya). A specific analysis focused on the slope landforms along the rock slopes. The study is based on fieldwork that defined deposits and landforms distribution of areas with different bedrock and geomorphological context. The analysis of the rock slopes focused on weathering and erosion processes, estimating erosion rates of 0.15–0.37 mm/yr over the Holocene, consistent with other areas around the Kongsfjorden and close to the highest values found in arctic areas.